A molecular tool for menstrual cycle phase dating of endometrial samples in endometriosis transcriptome studies. Issue 1 (20th April 2019) - Saare, Merli; Laisk, Triin; Teder, Hindrek; Paluoja, Priit; Palta, Priit; Koel, Mariann; Kirss, Fred; Karro, Helle; Sõritsa, Deniss; Salumets, Andres; Krjutškov, Kaarel; Peters, Maire
Abstract : Transcriptome profiling of 57 endometrial receptivity genes specifies the menstrual cycle phase of endometrial samples.